Phospholipase A2 of Peroxiredoxin 6 Plays a Critical Role in Cerebral Ischemia/Reperfusion Inflammatory Injury - Shanshan, Yu; Beibei, Jiang; Li, Tan; Minna, Gao; Shipeng, Lei; Li, Peng; Yong, Zhao (Frontiers in Cellular Neuroscience, 2017)
Microglia-mediated inflammation is an important step in the progression of cerebral ischemia/reperfusion injury and the associated production of receptors of immunomoudulation, including Toll-like receptors (TLRs). Peroxiredoxin 6 (Prdx6) has been demonstrated as the endogenous antioxidant protein for its peroxidase properties. However, the role of the iPLA2 activity of Prdx6 in stroke has not been well studied. In this study, we evaluated whether blocking the calcium-independent phospholipase A2 (iPLA2) activity of Prdx6 using siRNA and inhibitors (1-hexadecyl-3-(trifluoroethgl)-sn-glycerol-2 phosphomethanol, MJ33) would have a critical effect on inflammatory brain damage. We conducted oxygen-glucose deprivation/recovery (OGD/R) in vitro and middle cerebral artery occlusion (MCAO) in vivo in a microglia/neuron co-culture system and in rats. In vitro, we found that Prdx6-iPLA2 activity was associated with the secretion of neurotoxic inflammatory mediators interleukin1β (IL-1β), interleukin-17 (IL-17), and interleukin-23 (IL-23) and elevated expression of Toll-like receptor 2/4 (TLR2/4), leading to the formation of nuclear factor-kappa B (NF-κB), inducible nitric oxide synthase (iNOS), and cyclooxygenase-2 (COX-2) in microglial cells. In vivo, combined treatment with Prdx6-iPLA2 activity inhibitor MJ33 showed a greater diminution in neurologic deficits, cerebral infarction, brain water content, and inflammatory molecules than Prdx6-siRNA treatment alone. Our findings provide new insight into Prdx6-iPLA2 function in the brain. Inhibition of Prdx6-iPLA2 activity by gene therapy and/or pharmacology may constitute a promising new therapeutic approach to the treatment of stroke.